Pola Religius Social Support Komplementer Strategi Kolaborasi Keluarga Dan Pesantren Dalam Menguatkan Resiliensi Dan Karakter Beragama Santri Berlatar Belakang Rentan - Siti Fatimah Zahra; Noor Azida Batubara; Juwairiyah Nisa; Sutrisna Sutrisna; Defi Luthfiah; Siti Asiah Abdul Hadi (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze complementary religious social support (RSS) patterns as a collaborative strategy between families and Islamic boarding schools in strengthening the resilience and religious character of adolescents. This topic is important because it highlights the psychosocial vulnerability of adolescents from dysfunctional families (broken homes) who require consistent environmental intervention. This qualitative research with a case study design was conducted at the Darojatul Ashfad Islamic Boarding School, involving caregivers, parents, and students as subjects. The results showed that this collaboration formed a functioning mesosystem, characterized by its complementary nature. The Islamic boarding school strategically filled the deficit in family spiritual support (RSS) through regular meetings and a checklist of religious practices, ensuring continuity of rules. The effectiveness of this mesosystem is proven to strengthen the resilience of students through a shift in coping mechanisms, from reactive to Tawakkal. The attitude of Tawakkal serves as a psychological anchor that provides inner peace, breaks the chain of trauma, and ultimately leads to character internalization. This is evidenced by changes in the students' behavior, which has become automatic (such as the initiative to perform the dawn prayer without being told) and the emergence of concern for the condition of their families. It is concluded that complementary collaboration is an effective intervention model for shaping the resilience and religious character of vulnerable adolescents.